2018
DOI: 10.1038/s41467-018-05039-1
|View full text |Cite
|
Sign up to set email alerts
|

HHEX is a transcriptional regulator of the VEGFC/FLT4/PROX1 signaling axis during vascular development

Abstract: Formation of the lymphatic system requires the coordinated expression of several key regulators: vascular endothelial growth factor C (VEGFC), its receptor FLT4, and a key transcriptional effector, PROX1. Yet, how expression of these signaling components is regulated remains poorly understood. Here, using a combination of genetic and molecular approaches, we identify the transcription factor hematopoietically expressed homeobox (HHEX) as an upstream regulator of VEGFC, FLT4, and PROX1 during angiogenic sprouti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 70 publications
(84 reference statements)
2
66
0
Order By: Relevance
“…Mammalian TgfbrI / Alk5 has two paralogs in zebrafish, alk5a and alk5b , and from multiple datasets (Pauli et al, 2012; Yang et al, 2013; Gauvrit et al, 2018; Mullapudi et al, 2018), we found alk5b to be the highest expressed paralog during embryogenesis. To investigate its expression, we performed in situ hybridization and generated a transgenic reporter line, TgBAC ( alk5b:eGFP ), by bacterial artificial chromosome (BAC) recombineering (Figure S1).…”
Section: Resultsmentioning
confidence: 69%
“…Mammalian TgfbrI / Alk5 has two paralogs in zebrafish, alk5a and alk5b , and from multiple datasets (Pauli et al, 2012; Yang et al, 2013; Gauvrit et al, 2018; Mullapudi et al, 2018), we found alk5b to be the highest expressed paralog during embryogenesis. To investigate its expression, we performed in situ hybridization and generated a transgenic reporter line, TgBAC ( alk5b:eGFP ), by bacterial artificial chromosome (BAC) recombineering (Figure S1).…”
Section: Resultsmentioning
confidence: 69%
“…See Supplementary Table 9 for list of top 25 conserved marker genes. 48 TLS and embryo data were integrated as described above. For the analysis, the in vivo cell states were used as a reference, and compared to the TLS cells attributed to that cluster.…”
Section: Analysis Of Conserved Marker Genesmentioning
confidence: 99%
“…In adults, inflammation induces robust up-regulation of VEGFC expression by macrophages (Baluk et al, 2005). In addition, various hormones, transcription factors, metallothioneins, and microenvironmental stresses (e.g., hyperthermia, oxidative stress, and high salt) were shown to control VEGFC expression (Cohen et al, 2009;Machnik et al, 2009;Sapoznik et al, 2009;Chen et al, 2012;Schuermann et al, 2015;Gauvrit et al, 2018).…”
Section: Introductionmentioning
confidence: 99%